Comparison of Two-Port Verses Three-Port Laparoscopic Appendicectomy in CCM Medical and Hospital - Khare, Dr. Manish; Khanolkar, Dr. Ajay (International Journal of Innovative Research in Medical Science, 2018)
One of the most common cause of acute abdomen is acute appendicitis. A concept of ‘‘scarless’’ abdomen first described in 1998 by Esposito by Single Incision Laparoscopic Surgery was and has gained popularity. Still appendectomy is performed by laparotomy in most of the countries, causes may be the cost of the instruments or availability and affordability by the patients. Laparoscopic appendectomies are gaining popularity because of decreased pain, fewer postoperative complications, earlier mobilization, shorter hospitalization, earlier return to work, and better cosmesis. The aim of the study is to compare operative time, intra and post -operative complications, hospital stay after surgery in patients with two-port laparoscopic appendicectomy with the conventional three-port laparoscopic appendicectomy and to describe this technique for performing laparoscopic appendectomy with three portals at very low cost and with good aesthetic appearance and to compare the results with the conventional three-port laparoscopic appendicectomy. Material and Methods - Patients over the age of 18 with a diagnosis of acute abdomen, later on confirmed to acute appendicitis were included in the study. Out of 50 patients with laparoscopic appendicectomy, 23 for two port appendicectomy and 27 three port were included in the study. Hasson's technique was adopted for laproscopic access in to the abdomen. 10-mm umbilical port and 5-mm port was inserted with a grasper. Through the umbilical working trocar mesoappendix transected base of the appendix was ligated and the appendix was resected. Results - 23 cases performed using the two-port technique and 27 cases were performed using conventional 3 port technique. Operative time in two port appendicectomy (n=23) was 58±3.6 while in Conventional 3 port appendicectomy (n = 27) it was 52±2.4. Hospital stay for patients with two port appendicectomy was shorter and statistically significant. Conclusion - Two port appendicectomy is a safe and cost effective procedure and no major complications were found in this procedure.